MANAJEMEN KOLABORASI KURIKULUM SALAF DAN KHALAF DI PESANTREN DARUN NA’IM PONTIANAK - Samiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
At this time, Islamic boarding schools do not leave the traditions that have been determined together, nowadays Islamic boarding schools continue to carry out updates both in the field of management and institutions. The emergence of Islamic educational institutions is required to include character values in the curriculum and learning strategies implemented. Pesantren are expected not only to provide religious understanding but also to provide an understanding of general sciences. To produce santri who are not only superior in understanding religion but also superior in understanding general sciences, so that in the future pesantren produce outputs of religious experts who are faithful and intellectual as the curriculum that has been implemented at Pondok Pesantren Darunna'im Putri Pontianak City still uses the sorogan curriculum. Keywords: Curriculum Management, Collaboration of Salaf and Khalaf Curriculum, Pesantren